Migration and Dispersion of Heavy Metal Contaminants at Agbogbloshie-An Electronic Waste Recycling Site in Accra. - Asamoah, C.C. (University of Ghana, 2021)
Introduction: In Ghana, the unregulated recycling practices of individuals, in particular informal recyclers, and the lack of a well-structured management policy or strategy have resulted in environmental contamination through the release of heavy metals from some unconventional methods of recycling into surface soils. As such, heavy metals tend to penetrate deeper soil profile (toward the water table) and also migrate from the source of generation to surrounding soils and other media such as water in the environment. Objective: We investigated the movement of heavy metals from the focal point sources of generation across environmental media (soil and water) and the contamination associated with the informal recycling of e-waste. Methods: The study was an analytical cross-sectional study involving laboratory analysis of heavy metals in water and soil samples from the Odaw river and the Agbogbloshie e-waste dumpsite and nearby areas. Pb, Cd, As, and Hg were measured in 76 soil samples and six water samples taken at twenty-meter intervals using a handheld global positioning system to locate sampling points. Metal levels were measured using Atomic Absorption Spectrophotometer. We evaluated the individual contributions of each heavy metal to the total soil contamination using environmental pollution indices such as contamination factor, degree of contamination (Cdeg), and pollution load index and compared levels in water to permissible limits. Results: Results from soil analysis showed higher levels of Pb, Cd, As, and Hg in surface soils (58.77, 342.26, 4.82, 3.76) and subsoils (56.16, 210.16, 3.16, 2.20) at the main working area of burning. However, concentrations of Pb, As, Cd and Hg in surface and subsoils across all sampling areas exceeded their WHO/FAO thresholds for agricultural soils indicating that e-waste activities had an impact. In increasing order, Hg>As>Cd>Pb contributed significantly to the overall contamination degree of the surface soil and subsoil across job tasks. High accumulations of Pb, Cd, As, and Hg was also observed in water samples collected from Odaw river with the levels surpassing their permissible limits. Conclusion: Findings showed that the studied heavy metals are ubiquitous within surface soil and subsoil at Agbogbloshie and the higher levels of these metals were reflected in the environmental risk indices, indicating soil contamination at Agbogblshie beyond sources of generation to adjacent soils (residential, recreational, farming and commercial areas) as well as surface water (Odaw river). The present study demonstrated that urgent measures are needed to minimize heavy metals contamination resulting from e-waste recycling activities in Agbogblsohie, Accra.
MA. Public Health
Keywords: Ghana; Environmental contamination; Surface soils; Heavy metals; Metal levels